Mengenal kondisi lingkungan dan peserta didik MTsN 2 Malang: Field Study - Sirfa, Milchatin (Maliki Interdisciplinary Journal, 2024)
The character of students and the conditions of the school environment are two interrelated aspects in the world of education. This research aims to explore the relationship between student characteristics and environmental conditions at MTSN 2 Malang. The observation method is used to collect data about student behavior and environmental conditions at school. The results of the analysis show that the character of students is greatly influenced by the school environment. Therefore, integrated efforts are needed between schools, teachers and parents to strengthen the character formation of students and create a school environment that supports their growth holistically.